Filsafat Pendidikan Jean-Jacques Rousseau: Konsep 'Back to Nature' dan Relevansinya terhadap Implementasi Kurikulum Merdeka di Sekolah Dasar - Kevin, Alfredo; Wijanarko, Robertus (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2025)
The research study pays attention to the philosophical concept of ‘back to nature’ education according to Jean-Jacques Rousseau. His philosophical literature studies regarding educational ideas are contained in his famous work entitled “Emile” (1762) according to J.J Rousseau and his influence on the development of modern education. Specifically, for the implementation of the Independent Curriculum at the elementary school level in Indonesia today. In this research, the author uses a qualitative-descriptive method, namely describing the situation of implementing project-based learning in the Independent Curriculum in elementary schools and exploring Rousseau’s educational thoughts based on data obtained from literature studies. The theoretical framework is increasingly focused on Rousseau’s view of ‘back to nature’ education based on age groups; in this case it is childhood (2-12 years). As a result, the author found that the education pattern is a return to nature, meaning a return to human nature, where children as an educational subject should continue to improve their good educational competencies, specifically sensory development in childhood in line with the principles of a free and loving nature. This seems to be in line with the development of the Independent Curriculum which places children at the center of education so that they can learn freely, creatively with special skills in project-based and thematic learning programs, so that they can show their natural talents.